Perubahan Status Jenis Kelamin dalam Perspektif Hukum Positif di Indonesia - I Nyoman Satria Perwira; Ida Ayu Putu Widiati; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
Sexual abnormalities are caused by abnormalities in a person's hormones. Transsexuals have the desire to change their sex by means of surgery, which can be done in accordance with applicable procedures. Until now, Indonesia does not have a legal regulation regarding changing the sex status of a transgender person who performs sex surgery, because there are no rules on changing gender status, it creates a vacuum of norms and causes people to still underestimate a transgender person. Change of gender status can be made by submitting the application to the District Court. This study aims to explain the procedure for sex change in Indonesia and the legality of sex change from a positive legal perspective in Indonesia. This research used normative research and a conceptual approach. The sources of legal materials used were primary, secondary, and tertiary legal materials. Data obtained through documentation and recording techniques then analyzed systematically. The results showed that the change in gender status in Indonesia has several stages such as undergoing counseling, psychiatric examinations, andrology examinations, physical examinations, psychoreligious counseling, and others of an administrative nature. Not everyone can perform genital surgery, there are several conditions that must be met to get legality or legal certainty that a transgender person can file it in a local district court, this is done to get legal recognition.